Dizziness and balance disorders in the elderly - Aleksandra Modlińska; Aleksander Florczak; Natalia Krakowska; Marlena Kontowicz; Hubert Lange; Adrian Zwolinski; Ewa Rozmanowicz; Aleksandra Fortuna; Klaudia Kwiatkowska; Olga Rymarska; Beniamin Szmelcer; Michał Wilczyński; et al. (Kazimierz Wielki University, 2019)
Background: Patients in the geriatric age are characterized by the presence of degenerative changes, significantly affecting their daily functioning. One of the most common symptoms accompanying the elderly include dizziness and balance disorders. This is an extremely important issue, because even every third patient can report such ailments. Often, especially in the group of geriatric patients, these problems are related to disorders in the circulatory system, and more specifically to orthostatic hypotension. Material and methods: Analysis of available literature, articles in the Google Scholar and PubMed database using keywords: geriatrics, dizziness, balance disorders. Results: In the treatment of dizziness and disorders of the balance we distinguish pharmacological and non-pharmacological methods where kinesitherapy (exercises) looms large. In the case of pharmacological treatment, attention should be focused on causal therapy because symptomatic treatment can cause side effects and should therefore be used as soon as possible. In many cases, pharmacological treatment can be fully replaced by normal and individually conducted physiotherapeutic procedures. Training to which a patient is subjected should consist of many elements, which, however, will be adapted to the conditions that can meet a patient in everyday life. In diagnostics of the above-mentioned problems, research on stabilometric platforms is becoming more and more important. Increasingly, also in the rehabilitation of patients with a problem with equilibrium, modern technology in the form of virtual reality is used. Conclusions: Dizziness and balance disorders can result in many problems, which is why correct diagnosis and effective treatment are so important, especially because it is a problem for more and more people. Greater importance should be attached to prevention. Although modern forms of fighting these disorders are being introduced, there is still a need for further research on their effectiveness.